PRODUK GEL HAND SANITIZER SEBAGAI ANTISEPTIK DARI EKSTRAK KULIT JERUK MANIS (Citrus sinensis (L.)) - Erika Dwi Oktaviani; Melantina Oktriyanti; Nina Hartati (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
Various types of bacteria, viruses and fungi will be easier to stick to and thrive on unclean hands. Making people use products that contain antiseptics such as soap and hand sanitizer. However, in general, the basic ingredient for making antiseptics comes from alcohol. The development of antiseptic products can be done with natural ingredients such as using sweet orange peel (Citrus sinensis (L.)). It is known that sweet orange peel (Citrus sinensis (L.)) contains saponin, flavonoid, and tannin compounds which act as antibacterial so that it can be a natural antiseptic ingredient for making hand sanitizer gel. This study aims to determine the effect of maceration time and composition of sweet orange peel extract on antiseptic power in hand sanitizer gel preparations and can produce hand sanitizer products that are in accordance with SNI quality by varying the maceration time of the extract, namely 3 days, 5 days and 7 days the amount of sweet orange peel extract 5%, 10% and 15%. The product analysis of hand sanitizer gel includes organoleptic, homogeneity, pH, density, viscosity, dispersibility and bacteria. Based on the results of the analysis, all samples met the quality of SNI, but the best sample was 15% composition with a maceration time of 7 days. The results of the analysis showed that the pH value was 6, the density was 1.0470 gr/cm3, the viscosity was 578.08 cP, the dispersion was 8.3 cm.